Characteristics and short‐term obstetric outcomes in a case series of 67 women test‐positive for SARS‐CoV‐2 in Stockholm, Sweden. (5th November 2020) - Remaeus, Katarina; Savchenko, Julia; Brismar Wendel, Sophia; Brusell Gidlöf, Sebastian; Graner, Sophie; Jones, Elin; Molin, Johanna; Saltvedt, Sissel; Wallström, Tove; Pettersson, Karin
Abstract: Introduction: The Stockholm region was the first area in Sweden to be hit by the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). The national guidelines on the care of women with a positive test for SARS‐CoV‐2 (detection with polymerase chain reaction [PCR]) recommend individualized antenatal care, mode of delivery based on obstetric considerations, and no routine separation of the mother and the newborn. Breastfeeding is encouraged, and although there is no specific recommendation regarding wearing a face mask to prevent viral transmission to the newborn while nursing, instructions are given to keep high hygiene standards. All studies based on cases tested on hospital admission will capture more women with pregnancy complications than in the general population. Our aim was to describe the clinical characteristics of SARS‐CoV‐2‐positive women and their neonates, and to report short‐term maternal and neonatal outcomes. Material and methods: A retrospective case series with data from medical records including all test‐positive women (n = 67) who gave birth to 68 neonates from 19 March to 26 April 2020 in Stockholm, Sweden. Means, proportions and percentages were calculated for clinical characteristics and outcomes. Results: The mean age was 32 years, 40% were nulliparous and 61% were overweight or obese. Further, 15% had diabetes and 21% a hypertensive disease. Seventy percent of the women had a vaginal birth. Preterm delivery occurred in 19% of the women. The preterm deliveries were mostly medically indicated, including two women who were delivered preterm due to severe coronavirus disease 19 (COVID‐19), corresponding to 15% of the preterm births. Four women (6%) were admitted to the intensive care unit postpartum but there were no maternal deaths. There were two perinatal deaths (one stillbirth and one neonatal death). Three neonates were PCR‐positive for SARS‐CoV‐2 after birth. Conclusions: In this case series of 67 women testing positive for SARS‐CoV‐2 with clinical presentations ranging from asymptomatic to manifest COVID‐19 disease, few women presented with severe COVID‐19 illness. The majority had a vaginal birth at term with a healthy neonate that was negative for SARS‐CoV‐2.